Propuesta de indicadores de gestión para la medición de los recursos productivos e improductivos en las empresas de servicios hoteleros del D.M. de Quito - Paillacho Herrera, Danny Xavier (2014)
The hotel industry is one of the main sectors contributing to the economy, as representative figures generates money and contributes significantly to the generation of jobs, vital for the stability and growth of a country. As a major sector of the economy of a country requires tools and methods that help to have meaningful control by which management can take the most appropriate to achieve their objectives and goals in their strategic plans set earlier decisions.